Phenotype of patients with malignant melanoma and dysplastic and common nevi - Alekseenko, Ana; Wojas-Pelc, Anna; Wiśniowski, Zdzisław; Czerwińska, Magdalena (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction . Melanoma incidence rates have been increasing during the last decades in most countries throughout the world, especially among people with fair skin. Melanocytic nevi are diagnosed very often. Most of them are benign and rarely undergo neoplastic transformation. However, 30% of malignant melanomas develop from previously existing nevi. The best known and the most important melanoma risk factors are: UV radiation (natural and artificial – sun lamps), permanent mechanical or chemical irritation, fair skin phototype (I and II), numerous melanocytic nevi, and genetic factors. Objective . To analyse phenotypic features in patients with melanoma, dysplastic and common nevi and their incidence rates in different patient groups. Material and methods . 102 melanocytic skin lesions including 30 cases of common nevi, 38 cases of dysplastic nevi and 34 cases of melanoma were diagnosed by dermoscopy and excised. A personal questionnaire was used to analyse phenotypic features. The relationship between type of melanocytic lesion, eye colour, hair and skin phototype as well as other data were evaluated by nonparametric ANOVA rank, Kruskal-Wallis, Mann-Whitney tests with p < 0.05 condition for statistical significance. Results . The mean age of patients with melanoma was 65.2 years for men and 59.1 years for women and the difference was not statistically significant. In the melanoma group fair hair occurred more frequently than dark hair (91.2%; 31 vs. 3, p = 0.02225). Fair hair was also a dominant phenotypic feature among patients with dysplastic (26 vs. 2) and common nevi (22 vs. 8). 85.3% of patients with melanoma, 71.05% with dysplastic and 80% with common nevi had fair eyes. In the melanoma group a statistically significant difference was observed between patients with fair and dark skin phototype (p = 0.03676). Statistically significant differences in total nevi count were found between patients with melanoma. A high total nevi count (> 100) was observed in 64.7% of patients, and moderate total nevi count (21-100) in 35.3% of cases. In the melanoma group there were no patients with a low total nevi count (< 20) (p = 0.00001). There was a significant difference in total nevi count between patients with dysplastic and common nevi. Congenital melanocytic nevi (present vs. absent) were significantly less frequently found in comparison to the whole studied population (102 patients) in patients with malignant melanoma (p = 0.00440), patients with dysplastic nevi, and patients with common nevi (p = 0.01712). Conclusions . Fair hair, fair eyes and fair skin phototype are the dominant phenotypic features among patients with skin melanoma. Among patients with benign melanocytic lesions (common, dysplastic nevi) "fair phenotype" occurred more frequently than the "dark" one. Among our patients the most important melanoma risk factor was high total nevi count.